2020
DOI: 10.1002/adfm.202008172
|View full text |Cite
|
Sign up to set email alerts
|

Use of Elastic, Porous, and Ultrathin Co‐Culture Membranes to Control the Endothelial Barrier Function via Cell Alignment

Abstract: Porous membranes used in co‐culture enable the in vitro partitioning of cellular microenvironments, while still permitting physical and biochemical crosstalk between cells. Thus, features of the co‐culture membrane are crucial for recapitulating the physiological functions of co‐cultured cells. This study presents elastic, porous, and ultrathin membranes (EPUMs), which enhance cell–cell interactions and control cell alignment with surface topology created by stretching the membranes. The EPUM is fabricated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
1
16
1
Order By: Relevance
“…For example, the membranes from materials such as poly(ε-caprolactone) and poly(lactide-co-caprolactone) were successfully fabricated using electrospinning or solution casting with the thickness of 4 µm and 960 nm, respectively. [20,21] Despite the closer resemblance of the basement membrane physiology there is no control over pore distribution or size using these technologies. By using microelectromechanical systems (MEMS) fabrication technologies, it was possible to fabricate ultrathin membranes with thickness in the nanometer Traditional Transwell inserts with track-etched 10 μm thick polymer membranes have been intensively used for studying cellular barriers.…”
Section: Transwell-integrated 2 µM Thick Transparent Polydimethylsiloxane Membranes With Controlled Pore Sizes and Distribution To Model mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the membranes from materials such as poly(ε-caprolactone) and poly(lactide-co-caprolactone) were successfully fabricated using electrospinning or solution casting with the thickness of 4 µm and 960 nm, respectively. [20,21] Despite the closer resemblance of the basement membrane physiology there is no control over pore distribution or size using these technologies. By using microelectromechanical systems (MEMS) fabrication technologies, it was possible to fabricate ultrathin membranes with thickness in the nanometer Traditional Transwell inserts with track-etched 10 μm thick polymer membranes have been intensively used for studying cellular barriers.…”
Section: Transwell-integrated 2 µM Thick Transparent Polydimethylsiloxane Membranes With Controlled Pore Sizes and Distribution To Model mentioning
confidence: 99%
“…[28][29][30] While membrane thickness critically determines factors such as cell-cell interaction, stiffness of the substrate was shown to affect cell proliferation, motility, and surface marker expression. [21,[31][32][33] Cells sense the substrate on which they grow through focal adhesion points and generate signals based on the forces required to deform the matrix which is dependent on the elastic modulus of the substrate. [34,35] For comparison, silicon-based membranes have the elastic modulus in the hundred gigapascals range while the elastic modulus of the soft tissues (e.g., brain, heart, lung) is varying between 0.5-1 KPa.…”
Section: Introductionmentioning
confidence: 99%
“…10 Pore shape is another main characteristic of membrane pores that can control various cellular responses, particularly cell morphology, by guiding the formation of adhesion components. 30 In a recent study, Yoo et al developed elliptical pores with different levels of elongation and confirmed that both vascular endothelial and mesenchymal stem cells could show higher alignment and elongation on the more elongated elliptical pores. 30 Elongation and alignment were oriented with the major axis of the pores.…”
Section: Cell Spreading and Morphologymentioning
confidence: 87%
“…The membrane geometrical characteristics demonstrated to have crucial importance in the design of the in vitro models. These characteristics, however, are insufficient, and additional mechanical properties must be considered as well, as they have a significant impact on cellular behaviors ( Bastounis et al., 2019 ; Yoo et al., 2020 ). The brain elastic modulus is less than 2.4 kPa whereas all the synthetic semi-permeable porous membranes besides PDMS membranes range from 1 MPa to 3 MPa.…”
Section: In Vitro Models Of the Bbbmentioning
confidence: 99%